The Effectiveness of Learning Basic Mathematics through Dice Games for 5-6 Years Old at TKIT Al-Muslim - Saputra, Aswin; Fahrudin, Ahmad; Arman Syah Putra; Nurul Aisyah; V.H. Valentino (CV. Inara, 2021)
The background of this research is to find out the effectiveness of basic mathematics learning through early childhood dice games for children aged 5-6 years at TKIT Algebra, by knowing basic mathematics variables as variables that affect TKIT for children aged 5-6 years, and also using dice games in subjects. basic mathematics in learning. The research method was carried out to find out the results using quantitative survey tools to 100 parents of TKIT Algebra students who were randomly selected, using SPSS software in processing the data obtained from the survey conducted. The problem raised in this study is the effectiveness of basic mathematics on TKIT aged 5-6 years and dice game for TKIT age 5-6 years, whether the relationship between these variables. The results of this study are that there is a significant relationship between basic mathematics and TKIT aged 5-6 years and there is a relationship between dice games and TKIT aged 5-6 years, all supporting data results will be explained in this paper.